Efikasi diri dan kemampuan berpikir kritis mahasiswa: Regulasi diri dan motivasi akademik sebagai mediator: Students' self-efficacy and critical thinking skills: Self-regulation and academic motivation as mediators - Febriani, Evi; Soetjipto, Budi Eko; Eva, Nur; Rahmawati, Hetti (Persona:Jurnal Psikologi Indonesia, 2024)
The low critical thinking skills of students in Indonesia are a serious problem, characterized by minimal active participation in discussions, lack of analytical skills, and low learning motivation. This study aimed to analyze self-efficacy's role in shaping students' critical thinking skills through self-regulation and academic motivation as mediators. This study involved 384 randomly recruited from 63,556 students at one of the universities in Madura. The research instruments used were the critical thinking scale (α = 0.85), self-regulation scale (α = 0.82), academic motivation scale (α = 0.86), and self-efficacy scale (α = 0.88). All scales have met psychometric requirements and have been validated using Confirmatory Factor Analysis (CFA). Data were analyzed using Structural Equation Modeling (SEM). The results showed that self-regulation and academic motivation positively affect self-efficacy, which then becomes a mediator in improving students' critical thinking skills. This study emphasizes the importance of a holistic approach in Higher Education to develop critical thinking skills by strengthening students' internal factors. Implications for further research will be discussed.